Factors Related to the Presence of Aedes SP Larvae in Simpang III Sipin Village in 2024 - Berlian Oktiani Sukma; Guspianto Guspianto; Andree Aulia Rahmat; Fajrina Hidayati; Ismi Nurwaqiah Ibnu (Lembaga Pengembangan Kinerja Dosen, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health issue in Indonesia, particularly in endemic areas like Simpang III Sipin Village. This disease is transmitted by Aedes sp mosquitoes, and the presence of their larvae is a key indicator of the potential spread of DHF. Environmental conditions, such as water reservoirs and humidity, alongside community behaviors, play significant roles in supporting the growth of these mosquito larvae. Therefore, research is needed to identify the factors influencing the presence of Aedes sp larvae. Methods: This study utilized a cross-sectional design with a quantitative approach. The sample consisted of 143 households, selected using purposive sampling techniques. Data were collected via questionnaires and direct observations. Additionally, measurements of environmental conditions such as air humidity and temperature were taken using a hygrothermometer. The variables under study included knowledge, attitudes, behavior regarding water reservoir drainage (TPA), number of TPAs, air humidity, and air temperature. Results: Data analysis was conducted using the Chi-Square statistical test to determine the relationships between the variables. The results indicated that factors like knowledge level (p = 0.008), attitude (p = 0.008), behavior related to draining water reservoirs (p = 0.001), number of water reservoirs (p = 0.013), and air humidity (p = 0.004) were significantly related to the presence of Aedes sp larvae. However, air temperature did not show a significant relationship (p = 0.675). Conclusion: High humidity environments encourage the growth of mosquito larvae, and insufficient knowledge and inadequate preventive behaviors contribute to increased mosquito populations, exacerbating the risk of DHF transmission.